Effect of Swimming Exercise on Respiratory Muscle Strength and Respiratory Functions in Children with Autism. - Adin, Emine; Pancar, Zarife (Eurasian Journal of Medicine, 2023)
Objective: The aim of this study is to examine the effects of swimming exercise on respiratory muscle strength and respiratory functions in children with autism. Autism is a mental disorder that affects many areas such as sensory, cognitive, motor, and psycho-motor development in individuals. Materials and Methods: For this purpose, 15 individuals with autism, 8 of which were in the experimental group and 7 in the control group, participated in the study. The experimental group was subjected to swimming exercise for 1 hour, 3 days a week, for 6 weeks. The control group was not included in this exercise. Respiratory muscle strength and pulmonary function tests were applied to both groups before and after the 6-week period. The obtained data were analyzed using Statistical Package for Social Sciences Program Version 22.0. Values were presented as minimum, maximum, mean, standard deviation, and standard error. The Shapiro-Wilk test was used to test for normality. Paired-sample t-test was used for pre-test and post-test, and independent-sample t-test was used for intergroup analysis. Results: At the end of 6 weeks, according to the statistical analysis data, there was a significant difference in some of the respiratory function parameters of the experimental group (P < .05), and an improvement was observed in the respiratory muscle strength values, but no significant difference was found (P > .05). No significant difference was found in the respiratory functions of the control group as a result of respiratory muscle strength measurements (P > .05). Conclusion: As a result, we can say that swimming exercise is effective in improving respiratory muscle strength and respiratory functions in children with autism.